Improving Students’ Perception Towards Learning Mathematics: Impact of Teaching Application of Mathematics - Kasmin, Fauziah; Othman, Zuraini; Syed Ahmad, Sharifah Sakinah (EDUCATUM Journal of Science, Mathematics and Technology, 2019)
Numerous decisions in our daily lives require the ability to calculate, solve problems, and employ concepts and skills in mathematics. However, students always have bad perceptions in mathematics as this subject is often challenging for students to master. Reports on issues about students’ mathematical education have been raised by many mathematics educators. Among of the issues are about difficulties in understanding mathematical concepts, attitudes towards mathematics, low achievement in mathematics and many more. Hence, the aim of this study is to explore students’ perceptions and attitudes towards mathematics by analyzing the impact of teaching application of mathematics to the students. The data were collected from Computer Science students where each participant was assigned to complete self-reported and close ended questionnaire. In this study, examination on attitudes of student include engagement, confidence and importance of mathematics. Data were analyzed by measuring the difference of individual statements on percentage of agreeing in pre – Smart for mathematics and post – Smart for mathematics. The findings show that when students learned and exposed to the application of mathematics, their engagement, confidence and importance of mathematics increases. It can concluded that by exposing students the purpose of learning mathematics in computer science, students’ positive attitude towards mathematics can be developed and hence improve their interests in learning mathematics